2018
DOI: 10.1002/fsn3.697
|View full text |Cite
|
Sign up to set email alerts
|

Natural extracts from fresh and oven‐dried winemaking by‐products as valuable source of antioxidant compounds

Abstract: Winemaking by‐products are a natural source of antioxidant components; however, due to their highly perishable and seasonal nature, they may require a prior conservation step before being processed. Natural extracts from fresh and oven‐dried red grape agro‐industrial by‐products were obtained by ultrasound assisted extraction (UAE), using a hydroalcoholic solution as extracting solvent. Extracts were analyzed by HPLC‐DAD‐ESI‐MS, to know the feasibility of winemaking by‐products as natural sources of phenolic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
3
8
1
Order By: Relevance
“…As it can be seen, catechin was the most abundant phenolic compound in all extracts from both vintages, with a concentration range between 0.95 and 3.50 mg/g. This result is in agreement with other authors [10,23,38,39] who also identified catechin as one of the main polyphenolic compounds in grape stem extracts, and described similar concentration ranges than those obtained in the present study. Among the phenolic acids identified and quantified in the present study, gallic acid was the most abundant in all varieties and vintages, with concentration values from 0.12 to 1.29 mg/g.…”
Section: Phenolic Compoundssupporting
confidence: 94%
“…As it can be seen, catechin was the most abundant phenolic compound in all extracts from both vintages, with a concentration range between 0.95 and 3.50 mg/g. This result is in agreement with other authors [10,23,38,39] who also identified catechin as one of the main polyphenolic compounds in grape stem extracts, and described similar concentration ranges than those obtained in the present study. Among the phenolic acids identified and quantified in the present study, gallic acid was the most abundant in all varieties and vintages, with concentration values from 0.12 to 1.29 mg/g.…”
Section: Phenolic Compoundssupporting
confidence: 94%
“…Three different GP extracts were chemically and sensory studied; as expected, red grape extracts contained higher amounts of polyphenols than the white grape extracts. These results agree with previous studies where the concentrations of polyphenols were 10 -69 mg GAE/g for GP extracts from red Tempranillo variety [24][25][26][27] and 8 mg GAE/g for WGPE [28].…”
Section: Discussionsupporting
confidence: 93%
“…Comparable to other authors phenolic profiling of the extracts show similar amounts of flavan-3-ols, although extracts with a high concentration of gallic acid and procyanidins have not been detected [27,29]. Furthermore, there was also a difference between the two red grape extracts, as ERGPE was the only one to contain quantifiable amounts of anthocyanins (malvidin glucoside, petunidin glucoside, and delphinidin glucoside).…”
Section: Discussioncontrasting
confidence: 58%
“…In order to obtain phenolic-rich extracts, conventional extraction methods with organic solvents are commonly used [21]. These extraction technologies are highly polluting, labor-intensive, solvent consuming, and time consuming, so it is necessary to develop green alternative methods [22]. The ultrasound assisted extraction (UAE) could be one of the most suitable techniques [23], as it is very simple to use, requires relatively inexpensive apparatus, reduces the volume of solvent [24], uses acoustic energy and solvents to enhance the release and diffusion of phenolic compounds from various matrices [25], and allows to use green extraction solvents with a high efficiency due to the mechanical effects that it produces in the cellular structure of the matrix [26,27].…”
Section: Introductionmentioning
confidence: 99%